ANALISIS IMPLEMENTASI TAHAP PENERAPAN DAN OPERASI KLAUSUL 4.4 OHSAS 18001 : 2007 DI PT. GMF AEROASIA TANGERANG TAHUN 2015 - Dini Anggraeni Novitasari; Ekawati Ekawati; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Occupational Health and Safety Assessment Series (OHSAS) 18001 : 2007 is a series of standard and specifications for the design of an Occupational Health and Safety (OH&S) Management System. OHSAS 18001 : 2007 include 6 clauses and require to prevent incident, illness, and accident to improve its OH&S performance. The results of external audit that has been conducted by PT. Sucofindo found that there is still many nonconformities from clause 4.4 OHSAS. Furthermore, the implementation of OHSAS 18001 : 2007 in PT. GMF AeroAsia has not been evaluated. The purpose of this research is to monitoring activities of OH&S management system in PT. GMF AeroAsia. This research use qualitative methodology with observation and indepth interview with key person of PT. GMF AeroAsia as the main research methodology. The research results showed that PT. GMF AeroAsia has been implemented clause 4.4 OHSAS in accordance with the requirements of OHSAS 18001 : 2007 standard, but the company has to improve the quality by integrating the OH&S and Environmental management system by its policy, manual procedures, and workplan.